COMMUNICATION IN SCIENCE'S TRAJECTORY Interdiciplinary study of Communication. Mathematic, and Philosophy - Wuryanta, A.G Eka Wenats (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2009)
the process of communication science maturity there are three sciences that giving a huge contribution. Those are political science. sociology, and psychology. There are also undeniable contribution from another science like mathematical science (like Shannon 'use lo explain the basic process of comnnmication), linguistic (which help communication science lo understand message characteristic on language), biology (which help us to see that conununication is a system of communication net that related one and another). By understand of the roofs and significant contribution from several sciences to science. we have to understand that communication science is cm interdiciplinary science. The link between conununication and those diciplines outside the communication science make it really clear that communication are such as emergent science.